Perancangan alat inducsion heating pada pengolahan teh sangrai dengan teknologi energi terbarukan (solar cell) - Evrita Lusiana Utari (Teknoin, 2017)
Indonesia receives solar energy whose average daily energy radiation per unit area per unit time is about 4.8 kilowatts / m2. Solar energy is one of the most abundant, pollution-free, and optimally explored renewable energy sources. Indonesia located in the tropics is very suitable and has the potential to develop solar energy. In the utilization of solar energy, it is necessary to develop a technology capable of converting solar energy into the desired energy of electrical energy. The supply of electric energy during the day can still be controlled by solar cell, while at night controlled by Aki.This technology is known as solar cells or internationally known as solar cell or photovoltaic.Induction heating is the onset of heat on the metal exposed to the induction of the magnetic field, this is because the metal arising Eddy current or navel currents in a circular direction surrounding the magnetic field occurrence of the navel due to the magnetic induction that cause magnetic flux that penetrates the metal, causing heat metal.Designing Induction Heating Tool is a combination of solar cell technology with induction heating which benefits to the processing of tea production. This tool is able to induce the specimen so that the specimen becomes hot until it reaches the dry point reaches 100ºC. Power required to supply 300 Watt heater.